(untitled) - Mellissinos, Adrian C. (New York, 1966)
A revision of the leading text on experimental physics. The feature of this book that has made it one of the most loved texts on the subject is that it goes far beyond a mere description of key experiments in physics. The author successfully provides the reader with an understanding and appreciation of the 'physics' behind the experiments.
Keywords: Physics,Vật lý; Experiments,Thí nghiệm